Antihypertensive nano-ceuticales based on chitosan biopolymer: Physico-chemical evaluation and release kinetics. (20th May 2016) - Niaz, Taskeen; Shabbir, Saima; Manzoor, Shahid; Rehman, Asma; Rahman, Abdur; Nasir, Habib; Imran, Muhammad
Highlights: Antihypertensive Nano-ceuticals: Extended release with improved bioavailability. AFM/SEM studies revealed <100 nm size with homogenous dispersion. Drug dependant encapsulation efficiency varied from 87% to 92%. FTIR spectra revealed hydrogen bonding and interactions with NH group of chitosan. Abstract: Prime risk factor behind cardiovascular associated mortality and morbidity is hypertension. The main challenge with antihypertensive (AHT) drug therapy is their extreme hydrophobic nature and very low oral bio-availability; which result into higher dosage/frequency and associated side effects of drugs. The main objective of this study was to fabricate AHT nano-ceuticals in hydrophilic carriers of natural origin to improve drugs′ solubility, protection and sustained release. AHT nano-carrier systems (NCS) encapsulating captopril, amlodipine and valsartan were fabricated using chitosan (CS) polymer by ionic gelation assisted ultra-sonication method. Drug encapsulation efficiencies of 92 ± 1.6%, 91 ± 0.9% and 87 ± 0.5% were observed for captopril, valsartan and amlodipine respectively. Scanning electron microscopy (SEM) based analysis had revealed that captopril loaded polymeric NCS were regular, smooth and without any agglomeration. FTIR analyses of drug loaded and empty NCS demonstrated that drugs were molecularly dispersed inside the nanoparticles via week hydrogen bonding. Captopril and valsartan have demonstrated grafting reaction with NH group of chitosan. Zeta sizer results had confirmed that average size of chitosan nanoparticles was below 100 nm. Encapsulation of captopril had reduced the surface charge value from +52.6 ± 4.8 to +46.5 ± 5.2 mV. Controlled release evaluation of highly encapsulated drug captopril had revealed a slow release in vitro from NCS in physiological buffer. Thus, here reported innovative AHT nano-ceuticals of polymeric origin can improve the oral administration of currently available hydrophobic drugs while providing the extended-release function.